A Diagnostic Panel for Acquired Immune-Mediated Polyneuropathies Based on the Expression of lncRNAs - Hussen, Bashdar Mahmud; Nicknafs, Fwad; Hidayat, Hazha Jamal; Sayad, Arezou; Ghafouri-Fard, Soudeh; Taheri, Mohammad (Frontiers in Immunology, 2021)
Long non-coding RNAs (lncRNAs) have been shown to alter immune responses, thus contributing to the pathobiology of autoimmune conditions. We investigated the expression levels of ANRIL, PICART1, MALAT1, CCAT1, CCAT2, and CCHE1 lncRNAs in acute and chronic inflammatory demyelinating polyneuropathy (AIDP and CIDP). ANRIL, PICART1, MALAT1, CCAT1, CCAT2, and CCHE1 lncRNAs were significantly downregulated in individuals with both AIDP and CIDP compared with unaffected individuals. Gender-based comparisons also verified such downregulations in both male and female subjects compared with sex-matched unaffected controls for all lncRNAs. There was no significant difference in the expression of any of the lncRNAs between cases with AIDP and cases with CIDP. While the expression levels of ANRIL and PICART1 were significantly correlated in healthy subjects (r = 0.86, p = 8.5E-16), similar analysis in cases with AIDP and CIDP revealed no significant correlation. The most robust correlation among patients was detected between ANRIL and MALAT1 lncRNAs (r = 0.59, p = 3.52E-6). ANRIL, MALAT1, and PICART1 had the diagnostic power of 0.96, 0.94, and 0.92 in distinguishing between cases with CIDP and controls, respectively. A combination of all lncRNAs resulted in 0.95 diagnostic power with a sensitivity of 0.85 and specificity of 0.96 for this purpose. Diagnostic power values of these lncRNAs in differentiation between cases with AIDP and controls were 0.98, 0.95, and 0.93, respectively. The combinatorial diagnostic power reached 0.98 for differentiation between cases with AIDP and controls. The six-lncRNA panel could differentiate combined cases with AIDP and CIDP from controls with area under the curve (AUC), sensitivity, and specificity values of 0.97, 0.90, and 0.96, respectively. Collectively, the lncRNA panel is suggested as a sensitive and specific diagnostic panel for acquired immune-mediated polyneuropathies.